Integrasi Spirit Jama’ah dan Dakwah Jama’ah Muhammadiyah: Strategi Ideologis dalam Meneguhkan Islam Berkemajuan di Abad Kedua - abdul wafi; Musleh, Musleh; Ramadhan, Fahim Abu; Septiadi, Septiadi; Halili, Heri Rifhan (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
The Jama’ah Muhammadiyah Movement and Jama’ah-based Da’wah represent an institutional manifestation of Islamic reform (tajdid) that seeks to integrate spiritual, rational, and social praxis dimensions. This study is motivated by the need to understand how Muhammadiyah develops a model of collective da’wah that is not merely normative or moralistic, but also functions as an instrument of social transformation within the context of modern society. The purpose of this study is to analyze the theological construction, social strategies, and epistemological implications of the Jama’ah Muhammadiyah Movement as a model of community-based da’wah. This study employs a library research approach using content analysis to examine religious texts, official Muhammadiyah documents, and the works of key Muhammadiyah figures. The findings indicate that Jama’ah-based da’wah in Muhammadiyah is grounded in the principle of amar ma‘ruf nahi munkar, contextualized through the spirit of tajdid and modern rationality. Da’wah is conceptualized not only as a religious activity but also as a transformative social process that encompasses the fields of education, health, economy, and humanitarian engagement. Theoretically, this study contributes to the development of the epistemology of modern Islamic da’wah based on the jama’ah (collective) paradigm. Practically, it offers a model of progressive da’wah and social empowerment that is applicable and potentially replicable in a global context. These findings affirm Muhammadiyah’s relevance as a representation of moderate Islam oriented toward the formation of khairu ummah and the advancement of a just and universal civilization.